La salud mental : una visión acerca de su atención integral (2005)
ABSTRACT: This article raises a reflection about the necessity to approach the reality of mental health from a holistic perspective of the human being in his bio-psycho-social, cultural, and labor dimensions as well as of those related to the political-economic global model, considering that there is an emerging crisis in this scope which seems to be generating a multicausal humanitarian crisis within the framework of these spheres. The positive or negative experience by any alteration in the mentioned variables derives into a substrate of information that is transferred, processed and stored in the central nervous system. The information stored in this system influences the positive or negative ways through which the subject thinks and acts, and it also impacts his mental health. However, there is little conclusive information available on this matter. This is why an invitation to reflect and to take action on these issues is encouraged, promoting mental health, prevention of mental diseases, as well as the attention and rehabilitation in an integral way. That is to say, from the context where the person lives, thinks and feels, impelling the interchange of good practices and data and the accomplishment of interdisciplinary projects in the framework of a public policy in a social state of right. At the same time, it is important to stimulate and support the investigation on mental health and its promotion towards the identification of the possible causes of mind representations that can alter mental health, departing from the social representations as pseudosatisfactory images of the basic necessities that elude the cause of the problem. The aim of this reflection is to project the necessity to think interdisciplinarily about the assistance to mental health in Colombia focusing in the subject, and looking for individualized optimal treatment for the people with mental alteration, accompanying those human beings with empathy, understanding that they have their own personalities, characteristics and conducts according to an individual context, and also looking for treatment alternatives that are different from the pharmacologic ones and that can promote a better quality of life, because although medications can provide health, they can also simultaneously trigger another disease or can make more serious another one that already exists, and this is a good reason to use them with caution.